2017
DOI: 10.1021/acs.est.7b05039
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Wristband Passive Samplers Yield Highly Individualized Pesticide Residue Exposure Profiles

Abstract: Monitoring human exposure to pesticides and pesticide residues (PRs) remains crucial for informing public health policies, despite strict regulation of plant protection product and biocide use. We used 72 low-cost silicone wristbands as noninvasive passive samplers to assess cumulative 5-day exposure of 30 individuals to polar PRs. Ethyl acetate extraction and LC-MS/MS analysis were used for the identification of PRs. Thirty-one PRs were detected of which 15 PRs (48%) were detected only in worn wristbands, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 86 publications
1
48
1
Order By: Relevance
“…We used data from these wristbands to learn about chemical exposures in this population, including common chemical exposures, relations between chemical exposures, predictors of chemical exposures, and common chemical exposure profiles. Our findings suggest that these silicone wristbands can be successfully deployed within sensitive populations to assess multipollutant exposures, extending the potential uses of this technology beyond previously successful investigations ( 15 , 16 , 18 , 21 23 ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We used data from these wristbands to learn about chemical exposures in this population, including common chemical exposures, relations between chemical exposures, predictors of chemical exposures, and common chemical exposure profiles. Our findings suggest that these silicone wristbands can be successfully deployed within sensitive populations to assess multipollutant exposures, extending the potential uses of this technology beyond previously successful investigations ( 15 , 16 , 18 , 21 23 ).…”
Section: Discussionmentioning
confidence: 67%
“…This emerging technology has been applied in several settings (15), including the assessment of exposures to flame retardants among maternal-child pairs (21) and school children (18) and the assessment of exposures to pesticides among agricultural workers (22) and non-occupationally exposed persons (23). However, there is limited evidence characterizing their use among pregnant populations; to date, a single study has used the wristbands to assess exposures to PAHs among pregnant women (16) and no studies have reported on their use to assess multipollutant exposures of many chemical classes.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatographic cleanup procedures previously used for analysis of organic pollutants in wristbands include Florisil [12], C 18 solid phase extraction cartridges [4], and 5% acid silica columns [13]. Some other methods (mostly focusing on the screening of analytes) did not include any cleanup or fractionation [5,7,14]. In the initial trials, we found several interferences in the extracts that were limiting the analysis of some target analytes: one was siloxane, which was released from the wristbands during extraction; the other were lipids, which were transferred from the skin to the wristbands during deployment due to the direct skin-wristband contact.…”
Section: Chromatographic Cleanupmentioning
confidence: 99%
“…This study also provides a method that allows researchers to quantitatively compare hive chemical profiles without needing to determine compound concentrations in the air of each hive. Previous studies have shown that the consistent adsorption of silicone bands allow samples to be compared without the need for further calculations, provided the dimensions of the silicone sampler and deployment length are the same [ 25 , 48 ]. Silicone bands are more consistent in their compound adsorption ratios than several other passive samplers such as polyurethane foam, urine sampling, and hand wipes [ 25 , 26 ], potentially because the silicone matrix stabilizes compounds until extraction [ 24 ].…”
Section: Discussionmentioning
confidence: 99%